Community Structure and Ecological Network's Changes of Vaginal Microbiome in Women Right After Delivery - Hongping Li; Jingbo Jiang; Chuan Nie; Bin Xiao; Qingxia Li; Jieyang Yu (Frontiers Media S.A., 2022)
ObjectivesVaginal microbiota is not only an important source of bacterial colonization for neonates, but also plays a crucial role in maternal and neonatal health. This study aimed to investigate the vaginal microbial community structure right after delivery and its impact on the neonatal oral microbiome.MethodsIn this study, 27 women were recruited from Bao'an Maternal and Child Health Hospital. Bacterial compositions of vaginal samples before and right after delivery and neonatal oral samples right after birth were investigated using 16S rRNA sequencing of V3-V4 hyperregions.ResultsVaginal microbiome before delivery was dominated by the genus Lactobacillus. After delivery, the vaginal microbial community was altered, with significantly decreased proportion of Lactobacillus, increased alpha-diversity, and a more diverse ecological network. A large number subjects dominated by Lactobacillus species before delivery shifted to CST (community state type) IV after delivery. In addition, similar changes were observed in the neonatal oral microbiome, and its community profile was closer to vaginal samples after delivery than before delivery with principal coordinates analysis and microbial source tracking analysis.ConclusionThe vaginal microbiome was altered right after delivery and impacted the colonization of the neonatal oral microbiome in China. Further, it is vital to understand the longitudinal influence on maternal and neonatal health of vaginal microbiome community changes after delivery.